Highly Sensitive Colorimetric Assay for Determining Fe3+ Based on Gold Nanoparticles Conjugated with Glycol Chitosan - Kim, Kyungmin; Nam, Yun-Sik; Lee, Yeonhee; Lee, Kang-Bong (HINDAWI LTD, 2017)
A highly sensitive and simple colorimetric assay for the detection of Fe3+ ions was developed using gold nanoparticles (AuNPs) conjugated with glycol chitosan (GC). The Fe3+ ion coordinates with the oxygen atoms of GC in a hexadentate manner (O-Fe3+-O), decreasing the interparticle distance and inducing aggregation. Time-of-flight secondary ion mass spectrometry showed that the bound Fe3+ was coordinated to the oxygen atoms of the ethylene glycol in GC, which resulted in a significant color change from light red to dark midnight blue due to aggregation. Using this GC-AuNP probe, the quantitative determination of Fe 3+ in biological, environmental, and pharmaceutical samples could be achieved by the naked eye and spectrophotometric methods. Sensitive response and pronounced color change of the GC-AuNPs in the presence of Fe3+ were optimized at pH 6, 70 degrees C, and 300mM NaCl concentration. The absorption intensity ratio (A(700)/A(510)) linearly correlated to the Fe3+ concentration in the linear range of 0-180 mu M. The limits of detection were 11.3, 29.2, and 46.0nM for tap water, pond water, and iron supplement tablets, respectively. Owing to its facile and sensitive nature, this assay method for Fe 3+ ions can be applied to the analysis of drinking water and pharmaceutical samples.
Keywords: IONS; IRON; CHEMOSENSOR; REDUCTION; GENERATION; COMPLEX; FE(III); CITRATE; ZN(II); DOTS